PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI KEMENTERIAN PARIWISATA - Agustina Massora (Jurnal Manajemen FE-UB, 2022)
Abstract This study aims to determine the extent of the relationship between Leadership, Organizational Culture and Employee Performance of the Ministry of Tourism, and to find out how the influence of work environment and communication factors on employee work productivity. In this study, the authors distributed questionnaires to 52 respondents with a census sampling technique and the data analysis methods used were multiple regression and multiple correlation F test. Based on the calculations, the regression obtained Y = 9.853 + 0.377 X1 + 0.278 X2, which means that every increase in the work environment variable (X1) will be followed by an increase in work productivity, every increase in the communication variable (X2) will be followed by an increase in work productivity. With R = 0.888, this indicates that there is a strong and positive relationship between leadership and organizational culture and performance. This means that an increase in leadership and organizational culture leads to an increase in performance. From the test with the F hypothesis, it is known that the calculated F is 91.734 while the F table is 3.19 with dk in the numerator 2 (=k-1=3-1) and dk in the denominator n – k = 54 – 3 = 51. Because F count is greater than F table, Ho is rejected and Ha is accepted, meaning that there is a relationship between leadership (X1) and organizational culture (X2) on performance (Y). From the coefficient of determination of 78.9%, this shows that the influence of leadership and organizational culture is 78.9% on the increase in performance, while the remaining 21.1% is influenced by other variables not included in this research model. For further research, it is expected to add other variables related to work productivity such as organizational commitment, compensation, work environment and others, so that the influence of other factors that will affect performance can be better known.   Keywords: leadership, organizational culture, employee performance